Photon Absorption Models in Nanostructured Semiconductor Solar Cells and Devices - Luque, Antonio; Mellor, Alexander Virgil (SpringerBriefs in Applied Sciences and Technology,, 2015)
This book is intended to be used by materials and device physicists and also solar cells researchers. It models the performance characteristics of nanostructured solar cells and resolves the dynamics of transitions between several levels of these devices. An outstanding insight into the physical behaviour of these devices is provided, which complements experimental work. This therefore allows a better understanding of the results, enabling the development of new experiments and optimization of new devices. It is intended to be accessible to researchers, but also to provide engineering tools which are often only accessible to quantum physicists. Photon Absorption Models in Nanostructured Semiconductor Solar Cells and Devices is intended to provide an easy-to-handle means to calculate the light absorption in nanostructures, the final goal being the ability to model operational behaviour of nanostructured solar cells. It allows researchers to design new experiments and improve solar cell performances, and offers a means for the easy approximate calculation of the energy spectrum and photon absorption coefficients of nanostructures. This calculation is based on the effective mass model and uses a new Hamiltonian called the Empirical kp Hamiltonian, which is based on a four band kp model.